Drug-related problems in community-dwelling primary care patients screened positive for dementia. (7th August 2017) - Wucherer, D.; Thyrian, J. R.; Eichler, T.; Hertel, J.; Kilimann, I.; Richter, S.; Michalowsky, B.; Zwingmann, I.; Dreier-Wolfgramm, A.; Ritter, C. A.; Teipel, S.; Hoffmann, W.
ABSTRACT: Background: Older people have a higher risk of drug-related problems (DRPs). However, little is known about the prevalence of DRPs in community-dwelling people who screened positive for dementia. Our study aimed to determine (1) the prevalence and types of DRPs and (2) the socio-demographic and clinical variables associated with DRPs in people screened positive for dementia in primary care. Methods: The Dementia: life- and person-centered help in Mecklenburg-Western Pomerania (DelpHi-MV) study is a general practitioner (GP)-based cluster-randomized controlled intervention study to implement and evaluate an innovative concept of collaborative dementia care management in the primary care setting in Germany. Medication reviews of 446 study participants were conducted by pharmacists based on a comprehensive baseline assessment that included a computer-based home medication assessment. ClinicalTrials.gov Identifier: NCT01401582. Results: A total of 1, 077 DRPs were documented. In 414 study participants (93%), at least one DRP was detected by a pharmacist. The most frequent DRPs were administration and compliance problems (60%), drug interactions (17%), and problems with inappropriate drug choice (15%). The number of DRPs was significantly associated with the total number of drugs taken and with a formal diagnosis of a mental or behavioral disorder. Conclusions: Degree of cognitive impairment (MMSE defined) and formal diagnosis of dementia were not risk factors for an increased number of DRPs. However, the total number of drug taken and the presence of a diagnosis of mental and behavioral disorders were associated with an increased total number of DRPs.